Power analysis for single-case designs: Computations for (AB)k designs - Hedges, Larry V.; Shadish, William R.; Natesan Batley, Prathiba (Behavior research methods, 2023)
Currently, the design standards for single-case experimental designs (SCEDs) are based on validity considerations as prescribed by the What Works Clearinghouse. However, there is a need for design considerations such as power based on statistical analyses. We compute and derive power using computations for (AB) k designs with multiple cases which are common in SCEDs. Our computations show that effect size has the maximum impact on power followed by the number of subjects and then the number of phase reversals. An effect size of 0.75 or higher, at least one set of phase reversals (i.e., where k > 1), and at least three subjects showed high power. The latter two conditions agree with current standards about either having at least an ABAB design or a multiple baseline design with three subjects to meet design standards. An effect size of 0.75 or higher is not uncommon in SCEDs either. Autocorrelations, the number of time-points per phase, and intraclass correlations had a smaller but non-negligible impact on power. In sum, power analyses in the present study show that conditions to meet power requirements are not unreasonable in SCEDs. The software code to compute power is available on GitHub for the use of the reader.